MORPHOLOGY OF THE AQUATIC MOSSES COLLECTED IN LAKE YUKIDORI, LANGHOVDE, ANTARCTICA (Twelfth Symposium on Polar Biology) - カンダ, ヒロシ; オオタニ, シュウジ; KANDA, Hiroshi; OHTANI, Shuji (National Institute of Polar Research, 1991)
P(論文) Participating in the 29th Japanese Antarctic Research Expedition (JARE-29, 1987-1989), the authors collected aquatic mosses growing in Lake Yukidori, Langhovde near Syowa Station, East Antarctica. The moss specimens examined are mostly submerged forms of Bryum pseudotriquetrum (HEDW.) GAERTN., MEYERet SCHERB. which is usually characterized by elongate stems, loose foliation and short-obtuse leaf-apices. The moss specimens occasionally included a submerged form of Pottia heimii (HEDW.) HAMPE and were usually associated with some epiphytic algae. Ceratodon purpureus (HEDW.) BRID. which is one of the most abundant terrestrial moss species on the surrounding land, together with B. pseudotriquetrum, was not found in the lake. Ecological aspscts of the lake in which aquatic mosses occurred were surveyed and discussed. departmental bulletin paper